2019
DOI: 10.1186/s42269-019-0177-8
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of kaolin or potassium sulfate as anti-transpirant on improving physiological, biochemical aspects and yield of wheat plants under different watering regimes

Abstract: Background and objective: Certain substances with some physical and chemical activities can be used to decrease the transpiration rate and alleviate plant water stress through rising leaf resistance to the diffusion of water vapor. Wheat plant is considered as one of the most important and economic winter plants. So, the objective of this work is to evaluate the response of wheat plants (Triticum aestivum L.) cultivar Gimeza 7 to various concentrations of foliar application of anti-transpirant substances as ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…However, it is also worth stating that the extent of this effect may be varietal dependent and affected by the leaf water status [32]. Besides, the present effect of kaolin on promoting chlorophyll accumulation under stressful conditions, and thus preventing photo-oxidative damage, supports evidence from previous research on several crops, such as grapevines [14,38], wheat [39] and olive [29], and apple [40] trees.…”
Section: Discussionsupporting
confidence: 84%
“…However, it is also worth stating that the extent of this effect may be varietal dependent and affected by the leaf water status [32]. Besides, the present effect of kaolin on promoting chlorophyll accumulation under stressful conditions, and thus preventing photo-oxidative damage, supports evidence from previous research on several crops, such as grapevines [14,38], wheat [39] and olive [29], and apple [40] trees.…”
Section: Discussionsupporting
confidence: 84%
“…Kaolin treatments significantly reduced malondialdehyde levels in the second year (Table 5 ). As reported, by activating enzymatic systems in plants, kaolin protects the plant against environmental stresses and the cell membrane [ 85 ]. Wheat plant under drought stress treated with 3% kaolin foliar application had significantly lower levels of malondialdehyde than wheat without kaolin.…”
Section: Discussionmentioning
confidence: 99%
“…These results may be referred to that nano-particles have a diameter of less than 100 nm (6.36 -15.00 nm) as shown in Fig.1, where can easily penetrate through the stomata of leaves and translocate from leaves through the phloem sieve, where elements are then redistributed to plant parts (Wang et al 2013). Moreover, Abdallah et al (2019) mentioned that, in most plant species, K + has the major act for turgor changes in the guard cells during stomatal movement. An increase in K + concentration in the guard cells results in the uptake of water from the adjacent cells then the stomata opining.…”
Section: Stomatal Parametersmentioning
confidence: 92%
“…Zangeneh, Nayereh and Rasouli (2018) reported that the application of 1000 mg l -1 K-nano increased chlorophyll content but 2000 mg l -1 increased the potassium content and activity of the enzyme of grape fruit. Abdallah, Maha et al (2019) showed that, under drought, foliar application of K2SO4 (200 mg l -1 ) led to an increase in growth parameters, yield components, photosynthetic pigments, stomatal opening area in both upper and lower epidermis of wheat plant. Likewise, Jasim et al (2020) stated that spraying leaves of maize with 500 mg l -1 of nano potassium + 150 kg ha -1 of potassium sulphate fertilizer was superior for yield.…”
Section: Introductionmentioning
confidence: 99%